Therapeutic Repurposing Strategies for Cardiovascular Disease Management - Banerjee, Priyadarshini; Pradhan, Kishanta Kumar (Indian Journal of Pharmaceutical Education and Research, 2026)
Background: Anti-oxidants are vital in maintaining cellular homeostasis by neutralizing Reactive Oxygen Species (ROS) and mitigating oxidative stress. This review aims to explore their role in disease modulation, with a particular focus on cardiovascular disorders, including myocardial infarction and atherosclerosis. Materials and Methods: A comprehensive review of peer-reviewed literature was conducted to assess the biochemical mechanisms, efficacy, and clinical relevance of both natural and synthetic anti-oxidants. Anti-oxidants were found to significantly minimize damage from oxidative stress to lipids, proteins, and DNA. These effects contribute to decreased inflammatory responses, inhibition of LDL oxidation, and improvement in endothelial function, key factors in preventing atherosclerosis and myocardial damage. However, therapeutic outcomes vary depending on the type of anti-oxidant, dosage, and bioavailability. Results: Evidence demonstrates that anti-oxidants reduce oxidative damage, thereby inhibiting LDL oxidation and enhancing endothelial function. While preclinical data support their role in mitigating inflammatory responses, clinical efficacy remains inconsistent due to variations in dosage and bioavailability. Conclusion: The anti-oxidant's advantages in preventing disease and treatment are well-supported, with several key challenges remaining. Furthermore, clinical and translational research is scarce, with most findings derived from preclinical or observational studies. This review highlights these critical gaps by offering mechanistic insights and identifying future research directions.
Keywords: Anti-oxidants; Reactive Oxygen Species; Oxidative Stress; Biomarkers; Cardiovascular; Diseases